Marine Algae as a Potential Source for Anti-Obesity Agents - Chu Wan-Loy (Marine Drugs, 2016)
Obesity is a major epidemic that poses a worldwide threat to human health, as it is also associated with metabolic syndrome, type 2 diabetes and cardiovascular disease. Therapeutic intervention through weight loss drugs, accompanied by diet and exercise, is one of the options for the treatment and management of obesity. However, the only approved anti-obesity drug currently available in the market is orlistat, a synthetic inhibitor of pancreatic lipase. Other anti-obesity drugs are still being evaluated at different stages of clinical trials, while some have been withdrawn due to their severe adverse effects. Thus, there is a need to look for new anti-obesity agents, especially from biological sources. Marine algae, especially seaweeds are a promising source of anti-obesity agents. Four major bioactive compounds from seaweeds which have the potential as anti-obesity agents are fucoxanthin, alginates, fucoidans and phlorotannins. The anti-obesity effects of such compounds are due to several mechanisms, which include the inhibition of lipid absorption and metabolism (e.g., fucoxanthin and fucoidans), effect on satiety feeling (e.g., alginates), and inhibition of adipocyte differentiation (e.g., fucoxanthin). Further studies, especially testing bioactive compounds in long-term human trials are required before any new anti-obesity drugs based on algal products can be developed.